Another Image of ‘Community’ at the South End Museum - Smith, Michelle (Kronos: Southern African Histories, 2022)
This paper considers some of the curatorial devices used in exhibitions at the South End Museum in Gqeberha (formerly Port Elizabeth). The South End Museum, which opened on 3 March 2001, is modelled in several respects on the District Six Museum in Cape Town: it, too, is an urban-based, self-defined 'community museum' constituted around the histories of the apartheid Group Areas Act and the implementation of forced removals. Like many post-1994 museums in South Africa, the South End Museum relies on photographs for their displays, whilst also making use of maps, a mural and reenactment. The paper considers the ways in which these different displays touch, recall, reflect and activate one another. Keeping in mind that the notion of 'community' in South Africa bears the burden of being raced by its apartheid and colonial pasts, and abiding by the spectrality that is constitutive of the image, the paper grapples with the haunted space of 'community museums' in the Eastern Cape. While the South End Museum deploys some of the same curatorial devices as the District Six Museum, and deals with related histories of forced removal, South End, it is argued, brings the relation between race, indigeneity and 'ruin' within 'community museums' into fleeting focus.